Neurodevelopmental and psychosocial interventions for individuals with CHD: a research agenda and recommendations from the Cardiac Neurodevelopmental Outcome Collaborative - Cassidy, Adam R; Butler, Samantha C; Briend, Jennie; Calderon, Johanna; Casey, Frank; Crosby, Lori E; Fogel, Jennifer; Gauthier, Naomi; Raimondi, Carol; Marino, Bradley S; Sood, Erica; Butcher, Jennifer L (Cardiology in the young, 2021)
In 2018, the Neurodevelopmental and Psychosocial Interventions Working Group of the Cardiac Neurodevelopmental Outcome Collaborative convened through support from an R13 grant from the National Heart, Lung, and Blood Institute to survey the state of neurodevelopmental and psychosocial intervention research in CHD and to propose a slate of critical questions and investigations required to improve outcomes for this growing population of survivors and their families. Prior research, although limited, suggests that individualised developmental care interventions delivered early in life are beneficial for improving a range of outcomes including feeding, motor and cognitive development, and physiological regulation. Interventions to address self-regulatory, cognitive, and social-emotional challenges have shown promise in other medical populations, yet their applicability and effectiveness for use in individuals with CHD have not been examined. To move this field of research forward, we must strive to better understand the impact of neurodevelopmental and psychosocial intervention within the CHD population including adapting existing interventions for individuals with CHD. We must examine the ways in which dedicated cardiac neurodevelopmental follow-up programmes bolster resilience and support children and families through the myriad transitions inherent to the experience of living with CHD. And, we must ensure that interventions are person-/family-centred, inclusive of individuals from diverse cultural backgrounds as well as those with genetic/medical comorbidities, and proactive in their efforts to include individuals who are at highest risk but who may be traditionally less likely to participate in intervention trials.